Benign fibrous histiocytoma of the tongue - N S Priya; Kavita Rao; H S Umadevi; T Smitha (Wolters Kluwer Medknow Publications, 2013)
Benign fibrous histiocytoma (BFH) is a benign fibrohistiocytic neoplasm. It is documented to occur in all anatomic sites with a strong predilection for sun exposed skin surfaces. Intra oral occurrence of BFH comprises a lesser percentage of cases with tongue being the least reported site. We report a case of BFH of the tongue with an emphasis on its histogenesis and a review of the literature.